Comorbidity of cerebral palsy and epilepsy with autism in children - B. A. Abusueva; M. A. Askevova; M. D. Shanavazova; B. M. Nasrutdinova; M. Yu. Bobylova; A. S. Gadzhieva (Русский журнал детской неврологии)
Background. Cerebral palsy is often combined with epilepsy (up to about 50 % of children). The treatment of epilepsy limits the rehabilitation of cerebral palsy, and the rehabilitation of cerebral palsy often provokes epileptic seizures. Epilepsy in children with cerebral palsy is often manifested in a form of developmental and epileptic encephalopathy with spike-and-wave activation in sleep, which is characterized by epileptiform activity according to the type of benign epileptiform patterns of childhood with a high index on the electroencephalogram (up to 100 %), severe epileptic seizures of a status course, and mental disorders by type autism-like behavior (the so-called atypical autism) and disorders of speech communication. The problem of comorbidity of cerebral palsy, epilepsy and autism remains relevant and needs further study.Aim. To study the features of autism spectrum disorder in a group of children with a combination of cerebral palsy and epilepsy.Materials and methods. We examined 100 patients aged 3–10 years with various forms of cerebral palsy, combined with epilepsy, to identify the clinical features of autism spectrum disorder. Criteria for inclusion in the study: age 3–10 years; verified diagnosis of epilepsy in combination with cerebral palsy and autism spectrum disorder; informed consent of the patient’s parents to participate in the study. Criteria for exclusion from the study: severe somatic diseases and disorders of the sense organs (in particular, kyphoscoliosis, gastrostomy and others, as well as deafness, blindness); age less than 3 or more than 10 years.Results. The average age of visiting a psychiatrist was 5.4 ± 0.5 years. The reasons for visit were: violation of the communication (76 %), decreased eye contact (75 %), lack of compassion for surrounding or adjacent animals (100 %), dysphoric disorders (77.1 %), aggression (55 %), autoaggression (40 %), phobias (90 %), impaired speech development (18 %). Perinatal brain damage was diagnosed in 100 % of cases. Epilepsy was manifested by focal motor seizures. Patients with complex treatment (drugs and pedagogical correction) have more pronounced positive dynamics compared with patients who received only drug therapy or only rehabilitation (p <0.05).Conclusion. In children with a combination of cerebral palsy and epilepsy, the cause of autism is perinatal lesions of the central nervous system, as well as the severity of motor pathology and the presence of continued epileptiform activity on the electroencephalogram. Autism in this group of children requires timely recognition and medical and pedagogical correction.